Galerij Nova : Tentoonstellingsseizoen 1962-1963. - Galerij Nova, Mechelen (Mechelen : Publirama P.V.B.A., 1963)
Slabbinck, Rik ; Van Esbroeck, Leopold ; Van Elzen, Staf ; De Pauw, Gabriel ; De Sutter, Jules ; De Vries, Hubert ; Humblet, Theo ; Riedel, Helene ; Flameng, Jan ; Bosmans, Lode
boek